Diversity of Pacific Agathotanais (Peracarida: Tanaidacea) - Stępień, Anna; Jóźwiak, Piotr; Jakiel, Aleksandra; Pełczyńska, Alicja; Błażewicz, Magdalena (Frontiers in Marine Science, 2022)
Agathotanais is one of the seven genera classified into the family Agathotanaidae. So far, 12 species have been described for the genus, seven of which are known from the Pacific. However, considering the present poor state of knowledge on deep-sea environments, a much higher number of Agathotanais species than currently known can be suspected. Among the studied material, collected from below 1,000 m during five deep-sea expeditions in different parts of the Pacific Ocean, we identified eight species: two of them were already known to the science and five species were identified as new to knowledge and their formal description is presented in the paper: two from the North West Pacific (the Sea of Okhotsk and Kuril-Kamchatka Trench), two from the Central Pacific (Clarion-Clipperton Fracture Zone), and one from the Australian slope. The eighth Agathotanais species in our material was determined using a molecular approach, but it was represented by only one partially destroyed individual and could therefore not be formally described. The proportion of Agathotanais collected at the Sea of Okhotsk was the highest (22%), whereas the numbers were substantially lower for the Kuril-Kamchatka Trench, and the Central and the Southern Pacific. Molecular analyses confirmed the monophyly of Agathotanais and Paragathotanais and a close relationship between both genera. Moreover, a close relationship between the two Australian species was revealed. As a result of our findings, the number of species known from the Pacific increased from 5 to 11, with the total number of species in this genus increasing from 12 to 17. An updated identification key for Agathotanais species is given.